Carbon bridged biphenolate ligands in rare earth chemistry. (14th October 2022) - Shephard, Angus C. G.; Ali, Safaa H.; Deacon, Glen B.; Junk, Peter C.
Abstract : This review highlights rare earth biphenolates as they offer a diversity over simpler aryloxides, as well as their efficacy as catalysts and initiators in organic transformations and polymerisations. Abstract : Rare earth biphenolate species have become an increasingly studied series of complexes, owing to the diversity they offer over mononuclear aryloxide complexes, as well as their efficacy as catalysts and initiators in a range of organic transformations and polymerisation reactions. Compared to monodentate aryloxide ligands, biphenolate ligand systems are still in their infancy in rare earth coordination chemistry. In their limited use, the ligand 2, 2′-methylenebis(6- tert -butyl-4-methylphenol) (mbmpH2 ) has been a popular candidate. This review aims to highlight the chemistry that has been explored thus far with these carbon bridged lanthanoid biphenolate systems.